Coinheritance of a novel mutation on the hba1 gene: c.187delG (p.W62fsX66) [codon 62 (-G) (α1)] with the α212 patchwork allele and Hb S [β6(A3)Glu→Val, GAG>GTG; HBB: c.20A>T] - Scheps, Karen Gabriela (2013)
We describe a novel frameshift mutation on the HBA1 gene (c.187delG), causative of α-thalassemia (α-thal) in a Black Cuban family with multiple sequence variants in the HBA genes and the Hb S [β6(A3)Glu→Val, GAG>GTG; HBB: c.20A>T] mutation. The deletion of the first base of codon 62 resulted in a frameshift at amino acid 62 with a putative premature termination codon (PTC) at amino acid 66 on the same exon (p.W62fsX66), which most likely triggers nonsense mediated decay of the resulting mRNA. This study also presents the first report of the α212 patchwork allele in Latin America and the description of two new sequence variants in the HBA2 region (c.-614G>A in the promoter region and c.95+39 C>T on the first intron).